Method for preparing organic or inorganic perovskite by ball milling method
By using ball milling to process perovskite raw materials under an inert atmosphere, combined with precise process control, the problems of low purity and efficiency in the existing perovskite preparation process have been solved, achieving high-quality, low-cost large-scale production.
Patent Information
- Application Number
- CN202511003438.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-21
- Publication Date
- 2025-10-28
AI Technical Summary
Existing perovskite preparation methods are difficult to achieve high-quality, low-cost, and large-scale production. They also suffer from problems such as difficulty in accurately controlling the stoichiometry during preparation, imperfect crystal structure, low product purity, and low production efficiency, which limit the material properties.
Perovskite raw materials were mixed and ball-milled under an inert atmosphere. By controlling the ball milling speed, time, and grinding ball ratio, combined with sieving, ethanol washing, and vacuum drying steps, high-purity, highly crystalline perovskite powder was prepared.
This method achieves efficient and low-energy perovskite powder preparation, with high crystallinity and controllable particle size. It is applicable to both organic and inorganic perovskites, suitable for large-scale production, and avoids the adverse effects of high temperature on material properties.
Smart Images

Figure CN120842115A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of titanium ore preparation technology, and in particular to a method for preparing organic or inorganic perovskite by ball milling. Background Technology
[0002] Perovskites, as compounds with a unique crystal structure (general formula ABX3, where the A-site is a large-radius cation, the B-site is a relatively small-radius cation, and X is an anion), have shown great application potential in numerous fields. In the field of solar cells, perovskite solar cells possess advantages such as high efficiency, low cost, relatively simple manufacturing processes, and a wide spectral absorption range, and are widely considered a core direction for next-generation photovoltaic technology. Currently, the photoelectric conversion efficiency of small-area devices in the laboratory is comparable to that of crystalline silicon cells and still has room for improvement. In the field of lasers, the band gap of perovskite materials is tunable, enabling the generation of lasers from the near-infrared to the ultraviolet bands, potentially bringing breakthroughs to the development of tunable lasers. Furthermore, perovskites have also shown promising application prospects in catalysis, radiation detection, and other fields.
[0003] However, the properties of perovskite materials largely depend on their preparation methods. Common methods such as high-temperature solid-state synthesis typically require temperatures of 1000-1200℃, resulting in products with low purity, uneven particle size distribution, and unsuitability for temperature-sensitive perovskite systems. While the sol-gel method ensures strict control of stoichiometry, facilitates high purification, and produces small, uniformly distributed particles, it suffers from drawbacks such as significant shrinkage during processing, residual pores, high cost, and susceptibility to cracking during drying. Hydrothermal synthesis is influenced by numerous factors and is unsuitable for preparing water-sensitive starting materials. Precipitation methods, while simple and economical, have limitations in controlling product morphology and particle size.
[0004] Existing methods for preparing organic or inorganic perovskites are insufficient to meet the demands for high-quality, low-cost, and large-scale production of perovskite materials. During the preparation process, problems such as difficulty in precisely controlling the stoichiometry of the perovskite, imperfect crystal structures, low product purity, and low production efficiency frequently arise. These issues limit the performance of the prepared perovskite materials in practical applications; for example, in solar cells, they may lead to unstable photoelectric conversion efficiency and shortened lifespan. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing organic or inorganic perovskites by ball milling, which greatly reduces energy consumption and avoids the adverse effects of high temperature on material properties.
[0006] In order to solve the above technical problems, the technical solutions of the present invention are as follows:
[0007] A method for preparing organic or inorganic perovskite by ball milling, the method comprising:
[0008] Step 1: In a glove box protected by an inert atmosphere, weigh the organic and inorganic raw materials according to the stoichiometric ratio of perovskite, and selectively add additives to obtain a mixture; place the mixture in a ball mill equipped with a zirconia grinding jar and zirconia grinding balls and seal it.
[0009] Step 2: Place the sealed grinding jar from Step 1 into a planetary ball mill and ball mill it at a speed of 200 rpm to 800 rpm for 1 to 12 hours; wherein the mass ratio of grinding balls to material is 5:1 to 20:1, and the grinding balls are composed of small balls with a diameter of 1 mm and large balls with a diameter of 5 mm in a mass ratio of 7:3; the ball milling temperature is controlled at ≤50℃.
[0010] Step 3: Take out the product after ball milling reaction in step 2, sieve it, wash it with ethanol to remove residual additives, and then vacuum dry the washed product at 40°C for 2 hours to obtain crystalline perovskite powder.
[0011] Further, in step 1, in a glove box protected by an inert atmosphere, the organic and inorganic raw materials are weighed according to the stoichiometric ratio of perovskite, and auxiliary agents are selectively added to obtain a mixture, including:
[0012] Step 11: In a glove box protected by an inert atmosphere, weigh out the organic component AX and the inorganic component BX2 according to the stoichiometric ratio of the perovskite chemical formula ABX3, where A is formamidinyl, B is lead ion, and X is iodide ion.
[0013] Step 12: Selectively add 0.1 to 5 wt% of the total mass of the materials as an auxiliary agent;
[0014] Step 13: Place the mixture and zirconia grinding balls together into a zirconia grinding jar and seal the jar to maintain an inert atmosphere.
[0015] Furthermore, the mixture is placed in a ball mill equipped with a zirconia grinding jar and zirconia grinding balls and sealed, comprising:
[0016] The mixture obtained in step 13 is loaded into the zirconia grinding jar, and zirconia grinding balls are added;
[0017] Control the gradation of the grinding balls, with 1mm diameter small balls accounting for 70% of the total mass of the grinding balls and 5mm diameter large balls accounting for 30%;
[0018] Adjust the mass ratio of grinding balls to the mixture to 5:1 to 20:1;
[0019] Inert gas is introduced into the grinding jar to replace the air for more than 3 minutes;
[0020] The tank is sealed, and the pressure of the inert atmosphere inside the tank is maintained at 0.1 to 0.3 MPa.
[0021] Further, in step 2, the sealed grinding jar from step 1 is placed in a planetary ball mill and ball-milled at a speed of 200 rpm to 800 rpm for 1 to 12 hours; wherein the mass ratio of grinding balls to material is 5:1 to 20:1, and the grinding balls consist of small balls with a diameter of 1 mm and large balls with a diameter of 5 mm in a mass ratio of 7:3; the ball milling temperature is controlled at ≤50℃, including:
[0022] Secure the sealed grinding jar to the planetary disk of the planetary ball mill and start the ball mill;
[0023] The ball mill is operated at speeds ranging from 200 rpm to 800 rpm, wherein:
[0024] For the first third of the time: control the rotation speed at 600-800 rpm to promote raw material crushing and initial reaction;
[0025] In the last two-thirds of the time: reduce the speed to 200-400 rpm to optimize grain growth and crystallinity;
[0026] The tank temperature is monitored in real time and maintained at ≤50℃ through a circulating water cooling system.
[0027] The total ball milling time is 1 to 12 hours, during which the pressure fluctuation of the inert atmosphere inside the tank is ≤ ±0.05 MPa.
[0028] Further, in step 3, the product from the ball milling reaction in step 2 is taken out, sieved, washed with ethanol to remove residual additives, and then the washed product is vacuum dried at 40°C for 2 hours to obtain crystalline perovskite powder, including:
[0029] The product after ball milling in step 2 is sieved through a 200-2000 mesh sieve to separate the grinding balls from the perovskite powder.
[0030] Place the sieved powder in a container, add ethanol at a solid-liquid ratio of 1g:10mL, and sonicate for 5-10 minutes to disperse the agglomerated particles.
[0031] Repeat the washing process 2 to 3 times until the light transmittance of the washing solution is ≥95%;
[0032] The washed powder was dried at 40℃ and under a vacuum of -0.1MPa for 2 hours to obtain perovskite powder with a particle size of 50nm to 2μm and a crystallinity of >95%.
[0033] Furthermore, the additive is oleic acid or a low-melting-point quaternary ammonium salt.
[0034] The above-described solution of the present invention has at least the following beneficial effects:
[0035] First, the preparation is highly efficient and energy-saving. This method employs planetary ball milling, and by appropriately setting the milling speed from 200 rpm to 800 rpm, the milling time from 1 hour to 12 hours, and the mass ratio of grinding balls to materials from 5:1 to 20:1, the raw materials can achieve a complete reaction in a relatively short time. Compared to traditional high-temperature solid-state methods that often involve temperatures exceeding 1000 degrees Celsius and prolonged heating, this invention controls the milling temperature to ≤50℃, significantly reducing energy consumption while avoiding the adverse effects of high temperatures on material properties. This makes it particularly suitable for temperature-sensitive organic perovskite systems.
[0036] Secondly, the product exhibits high purity and good crystallinity. In step 1, the raw materials are weighed and sealed within a glove box under an inert atmosphere, effectively preventing contamination of the raw materials and product by impurities such as water and oxygen in the air. The grinding balls consist of 1mm diameter small balls and 5mm diameter large balls in a 7:3 mass ratio. This combination creates a more efficient grinding effect, allowing the material to undergo more uniform and thorough impact and grinding, promoting full contact and reaction between raw materials, and reducing the residue of unreacted materials. Subsequent steps such as sieving, ethanol washing to remove residual additives, and vacuum drying at 40℃ further improve the purity of the product, resulting in a highly crystallized crystalline perovskite powder.
[0037] Furthermore, this method is not only applicable to the preparation of inorganic perovskites, but can also effectively prepare organic perovskites, solving the problem of poor compatibility with organic components in some traditional methods. The entire preparation process does not require complex equipment or harsh reaction conditions, and the operation steps are simple and controllable, making it easy to achieve large-scale production. At the same time, by selectively adding additives, the reaction process can be adjusted according to the needs of different perovskite systems, improving the flexibility of preparation.
[0038] Finally, a zirconia grinding jar and grinding balls are used, which have good chemical stability and will not react chemically with the raw materials and products, thus ensuring the purity and performance stability of the products. The parameters in the preparation process are easy to control, the products have good repeatability, and high-quality perovskite powder can be produced stably. Attached Figure Description
[0039] Figure 1 This is a schematic diagram of a method for preparing organic or inorganic perovskite by ball milling, provided by an embodiment of the present invention. Detailed Implementation
[0040] Exemplary embodiments of the present disclosure will now be described in more detail with reference to the accompanying drawings. While exemplary embodiments of the present disclosure are shown in the drawings, it should be understood that the present disclosure may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the disclosure to those skilled in the art.
[0041] Example 1
[0042] Raw material preparation: In a glove box filled with argon (inert atmosphere), weigh 1.58g of formamidinium iodide (FAI) and 3.31g of lead iodide (PbI2) according to the stoichiometric ratio of formamidinium lead iodide (FAPbI3) (1:1), add 0.049g of oleic acid (1wt% of the total material mass) as an auxiliary agent, and mix evenly to obtain a mixture.
[0043] Grinding jar sealing: Transfer the mixture into a 50mL zirconia grinding jar, add zirconia grinding balls (70% small balls with a diameter of 1mm and 30% large balls with a diameter of 5mm), and control the mass ratio of grinding balls to material to be 10:1 (i.e., 4.9g of grinding balls). Purge the jar with argon gas to replace the air, continue for 5 minutes, then seal the jar and maintain the pressure inside the jar at 0.2MPa.
[0044] Ball milling reaction: The grinding jar was fixed on the planetary disk of a planetary ball mill, and the total ball milling time was set to 6 hours. The first 2 hours (1 / 3 of the total time) were run at 800 rpm, and the speed was reduced to 300 rpm for the next 4 hours (2 / 3 of the total time). The jar temperature was controlled to be ≤45℃ through a circulating water cooling system, and the pressure fluctuation inside the jar was ≤±0.03MPa.
[0045] Post-processing: After ball milling, the product was removed and sieved through a 500-mesh sieve to separate the grinding balls. The resulting powder was ultrasonically washed three times (8 minutes each time) with ethanol at a solid-liquid ratio of 1g:10mL until the transmittance of the washing solution reached 96%. The washed powder was dried at 40℃ and a vacuum of -0.1MPa for 2 hours to obtain FAPbI3 perovskite powder.
[0046] Product characteristics: The powder particle size is 350 nm to 1.2 μm, and X-ray diffraction (XRD) analysis shows that the crystallinity is 97.2%.
[0047] Example 2
[0048] Raw material preparation: In a glove box under nitrogen protection, weigh 3.16g of FAI and 6.62g of PbI2 according to the stoichiometric ratio of FAPbI3, add 0.293g of low melting point quaternary ammonium salt (tetrabutylammonium chloride) accounting for 3wt% of the total material mass, and mix evenly.
[0049] Grinding jar sealing: Transfer the mixture into a 100mL zirconia grinding jar, add grinding balls (70% 1mm small balls + 30% 5mm large balls), and control the grinding ball to material mass ratio to be 15:1 (i.e., 14.65g of grinding balls). Purge the air with nitrogen for 6 minutes, then seal the jar, maintaining the pressure inside at 0.15MPa.
[0050] Ball milling reaction: The total ball milling time was 12 hours. The raw materials were crushed and initially reacted at 600 rpm for the first 4 hours, and then the speed was reduced to 200 rpm for the next 8 hours to optimize crystallization. The temperature was controlled to be ≤50℃ and the pressure fluctuation was controlled to be ≤±0.04MPa through a water cooling system.
[0051] Post-processing: After sieving through an 800-mesh sieve, the product was ultrasonically washed twice with ethanol at a ratio of 1g:10mL (10 minutes each time), and the transmittance of the washing solution reached 95.5%. After vacuum drying at 40℃ for 2 hours, FAPbI3 powder was obtained.
[0052] Product characteristics: Powder particle size is 120nm~800nm, and XRD analysis shows crystallinity of 96.8%.
[0053] Example 3
[0054] Raw material preparation: In an argon glove box, weigh 0.79g of FAI and 1.65g of PbI2 according to the stoichiometric ratio of FAPbI3, without adding any additives, and mix them directly until homogeneous.
[0055] Grinding jar sealing: Transfer the mixture into a 25mL zirconia grinding jar, add grinding balls (70% 1mm small balls + 30% 5mm large balls), and control the mass ratio of grinding balls to material to be 5:1 (i.e., 2.44g of grinding balls). Purge the air with argon gas for 3 minutes, then seal the jar. The pressure inside the jar should be 0.3MPa.
[0056] Ball milling reaction: The total ball milling time is 3 hours. The reaction speed is 700 rpm for the first hour and then reduced to 400 rpm for the next 2 hours. The water cooling system controls the temperature to ≤48℃ and the pressure fluctuation to ≤±0.02MPa.
[0057] Post-processing: After sieving through a 200-mesh sieve, the product was ultrasonically washed twice with ethanol at a ratio of 1g:10mL (5 minutes each time), and the transmittance of the washing solution reached 97%. After vacuum drying at 40℃ for 2 hours, FAPbI3 powder was obtained.
[0058] Product characteristics: Powder particle size is 500nm~2μm, and the crystallinity is 95.5% according to XRD analysis.
[0059] Example 4
[0060] Raw material preparation: In an argon-protected glove box, weigh 2.37g of FAI and 4.97g of PbI2 according to the stoichiometric ratio of FAPbI3, add 0.037g of low-melting-point quaternary ammonium salt (tetraethylammonium chloride) as an auxiliary agent, accounting for 0.5wt% of the total material mass, and mix evenly to obtain a mixture.
[0061] Grinding jar sealing: Place the mixture into a 100mL zirconia grinding jar, add zirconia grinding balls (70% small balls with a diameter of 1mm and 30% large balls with a diameter of 5mm), and control the mass ratio of grinding balls to material to be 15:1 (i.e., 11.08g of grinding balls). Purge the jar with argon gas to replace the air, continue for 4 minutes, then seal the jar, maintaining the inert atmosphere pressure inside the jar at 0.25MPa.
[0062] Ball milling reaction: The sealed grinding jar was fixed on the planetary disk of the planetary ball mill, and the ball mill was started. The total ball milling time was 9 hours. The first 3 hours (1 / 3 of the total time) were run at 700 rpm to promote raw material crushing and initial reaction; the speed was reduced to 250 rpm for the next 6 hours (2 / 3 of the total time) to optimize grain growth and crystallinity. The jar temperature was monitored and controlled in real time through a circulating water cooling system to keep it ≤48℃, and the inert atmosphere pressure inside the jar fluctuated within ±0.04 MPa.
[0063] Post-processing: After ball milling, the product was sieved through an 800-mesh sieve to separate the grinding balls from the perovskite powder. The sieved powder was placed in a container, and ethanol was added at a solid-liquid ratio of 1g:10mL. The mixture was ultrasonically vibrated for 7 minutes to disperse the agglomerated particles. The washing operation was repeated 3 times, at which point the transmittance of the washing solution reached 96.5%. The washed powder was dried at 40℃ and a vacuum of -0.1MPa for 2 hours to obtain FAPbI3 perovskite powder.
[0064] Product characteristics: The powder particle size is 200nm~1.5μm, and the crystallinity is 97.5% according to XRD analysis.
[0065] Example 5
[0066] Raw material preparation: In a glove box under nitrogen protection, weigh 0.395g of FAI and 0.828g of PbI2 according to the stoichiometric ratio of FAPbI3, add 0.061g of oleic acid (5wt% of the total material mass) as an auxiliary agent, and mix evenly to obtain a mixture.
[0067] Grinding jar sealing: Place the mixture in a 25mL zirconia grinding jar, add zirconia grinding balls (70% small balls with a diameter of 1mm and 30% large balls with a diameter of 5mm), and adjust the mass ratio of grinding balls to the mixture to 20:1 (i.e., 2.44g of grinding balls). Purge the jar with nitrogen to replace the air, continue for 3 minutes, then seal the jar, maintaining the inert atmosphere pressure inside the jar at 0.1MPa.
[0068] Ball milling reaction: Fix the grinding jar on the planetary disk of the planetary ball mill, start the ball mill, and the total ball milling time is 3 hours. For the first hour (1 / 3 of the total time), run at a speed of 600 rpm, and for the next 2 hours (2 / 3 of the total time), reduce the speed to 400 rpm. Control the jar temperature ≤50℃ through a circulating water cooling system, and the pressure fluctuation inside the jar ≤±0.05MPa during the process.
[0069] Post-processing: The ball-milled product was sieved through a 2000-mesh sieve to separate the grinding balls from the powder. The sieved powder was then mixed with ethanol at a solid-liquid ratio of 1g:10mL, ultrasonically vibrated for 10 minutes, and washed twice. The transmittance of the washing solution was 95.8%. The powder was dried at 40℃ and a vacuum of -0.1MPa for 2 hours to obtain FAPbI3 perovskite powder.
[0070] Product characteristics: The powder particle size is 50nm~800nm, and XRD analysis shows that the crystallinity is 96.3%.
[0071] Example 6
[0072] Raw material preparation: In an argon-protected glove box, weigh 4.74g of FAI and 9.94g of PbI2 according to the stoichiometric ratio of FAPbI3, add 0.442g of low-melting-point quaternary ammonium salt (tetrapropylammonium chloride) as an auxiliary agent accounting for 3wt% of the total material mass, and mix evenly to obtain a mixture.
[0073] Grinding jar sealing: Place the mixture into a 200mL zirconia grinding jar, add zirconia grinding balls (70% small balls with a diameter of 1mm and 30% large balls with a diameter of 5mm), and control the mass ratio of grinding balls to material to be 8:1 (i.e., 35.85g of grinding balls). Purge the jar with argon gas to replace the air, continue for 6 minutes, then seal the jar, maintaining the pressure inside the jar at 0.18MPa.
[0074] Ball milling reaction: Fix the grinding jar on the planetary disk of the planetary ball mill, start the ball mill, and the total ball milling time is 12 hours. For the first 4 hours (1 / 3 of the total time), run at a speed of 650 rpm, and for the next 8 hours (2 / 3 of the total time), reduce the speed to 350 rpm. The tank temperature is controlled to ≤46℃ through a circulating water cooling system, and the pressure fluctuation inside the tank is ≤±0.03MPa during the period.
[0075] Post-processing: The ball-milled product was sieved through a 1000-mesh sieve to separate the grinding balls from the powder. The sieved powder was then mixed with ethanol at a solid-liquid ratio of 1g:10mL, ultrasonically vibrated for 9 minutes, and washed three times. The transmittance of the washing solution reached 97%. The powder was dried at 40℃ and a vacuum of -0.1MPa for 2 hours to obtain FAPbI3 perovskite powder.
[0076] Product characteristics: The powder particle size is 400 nm to 1.8 μm, and the crystallinity is 98.1% as determined by XRD analysis.
[0077] Example 7
[0078] Raw material preparation: In an argon-protected glove box, weigh 1.0g of FAI and 2.09g of PbI2 according to the stoichiometric ratio of FAPbI3, add 0.003g of low-melting-point quaternary ammonium salt (tetrabutylammonium bromide) as an auxiliary agent, accounting for 0.1wt% of the total material mass, and mix evenly to obtain a mixture.
[0079] Grinding jar sealing: Place the mixture into a 50mL zirconia grinding jar, add zirconia grinding balls (70% small balls with a diameter of 1mm and 30% large balls with a diameter of 5mm), and control the mass ratio of grinding balls to material to be 8:1 (i.e., 24.7g of grinding balls). Purge the jar with argon gas to replace the air, continue for 4 minutes, then seal the jar, maintaining the inert atmosphere pressure inside the jar at 0.22MPa.
[0080] Ball milling reaction: The sealed grinding jar was fixed on the planetary disk of a planetary ball mill, and the ball mill was started. The total ball milling time was 4 hours. The first 4 / 3 hours (1 / 3 of the total time) were run at 750 rpm to promote raw material crushing and initial reaction; the speed was reduced to 300 rpm for the last 8 / 3 hours (2 / 3 of the total time) to optimize grain growth and crystallinity. The jar temperature was monitored in real time through a circulating water cooling system and maintained at ≤49℃. During this period, the inert atmosphere pressure inside the jar fluctuated within ±0.02 MPa.
[0081] Post-processing: After ball milling, the product was sieved through a 1200-mesh sieve to separate the grinding balls from the perovskite powder. The sieved powder was placed in a container, and ethanol was added at a solid-liquid ratio of 1g:10mL. The mixture was ultrasonically vibrated for 6 minutes to disperse the agglomerated particles. The washing operation was repeated twice, at which point the transmittance of the washing solution reached 95.2%. The washed powder was dried at 40℃ and a vacuum of -0.1MPa for 2 hours to obtain FAPbI3 perovskite powder.
[0082] Product characteristics: The powder particle size is 600nm~1.8μm, and the crystallinity is 96.0% according to XRD analysis.
[0083] Example 8
[0084] Raw material preparation: In a glove box under nitrogen protection, weigh 4.0g of FAI and 8.36g of PbI2 according to the stoichiometric ratio of FAPbI3, add 0.247g of oleic acid (2wt% of the total material mass) as an auxiliary agent, and mix evenly to obtain a mixture.
[0085] Grinding jar sealing: Place the mixture into a 200mL zirconia grinding jar, add zirconia grinding balls (70% small balls with a diameter of 1mm and 30% large balls with a diameter of 5mm), and adjust the mass ratio of grinding balls to the mixture to 12:1 (i.e., 148.3g of grinding balls). Purge the jar with nitrogen to replace the air, continue for 5 minutes, then seal the jar, maintaining the inert atmosphere pressure inside the jar at 0.12MPa.
[0086] Ball milling reaction: Fix the grinding jar on the planetary disk of the planetary ball mill, start the ball mill, and the total ball milling time is 8 hours. For the first 8 / 3 hours (1 / 3 of the total time), run at a speed of 650 rpm, and for the last 16 / 3 hours (2 / 3 of the total time), reduce the speed to 350 rpm. The jar temperature is controlled to ≤47℃ through a circulating water cooling system, and the pressure fluctuation inside the jar is ≤±0.04MPa during the process.
[0087] Post-processing: The ball-milled product was sieved through a 1500-mesh sieve to separate the grinding balls from the powder. The sieved powder was then mixed with ethanol at a solid-liquid ratio of 1g:10mL, ultrasonically vibrated for 9 minutes, and washed three times. The transmittance of the washing solution was 97.0%. The powder was dried at 40℃ and a vacuum of -0.1MPa for 2 hours to obtain FAPbI3 perovskite powder.
[0088] Product characteristics: The powder particle size is 150 nm to 1.0 μm, and XRD analysis shows that the crystallinity is 98.0%.
[0089] Example 9
[0090] Raw material preparation: In an argon-protected glove box, weigh 0.5g of FAI and 1.045g of PbI2 according to the stoichiometric ratio of FAPbI3, without adding any additives, and mix them evenly to obtain a mixture.
[0091] Grinding jar sealing: Place the mixture in a 25mL zirconia grinding jar, add zirconia grinding balls (70% small balls with a diameter of 1mm and 30% large balls with a diameter of 5mm), and control the mass ratio of grinding balls to material to be 20:1 (i.e., 31.0g of grinding balls). Purge the jar with argon gas to replace the air, continue for 3 minutes, then seal the jar and maintain the pressure inside the jar at 0.3MPa.
[0092] Ball milling reaction: Fix the grinding jar on the planetary disk of the planetary ball mill, start the ball mill, and the total ball milling time is 1 hour. Run at 800 rpm for the first 1 / 3 hour, and reduce the speed to 200 rpm for the last 2 / 3 hour. Control the jar temperature ≤50℃ through a circulating water cooling system, and the pressure fluctuation inside the jar ≤±0.05MPa during the process.
[0093] Post-processing: The ball-milled product was sieved through a 200-mesh sieve to separate the grinding balls from the powder. The sieved powder was then mixed with ethanol at a solid-liquid ratio of 1g:10mL, ultrasonically vibrated for 5 minutes, and washed twice. The transmittance of the washing solution reached 95.5%. The powder was dried at 40℃ and a vacuum of -0.1MPa for 2 hours to obtain FAPbI3 perovskite powder.
[0094] Product characteristics: The powder particle size is 800nm~2μm, and the crystallinity is 95.8% as determined by XRD analysis.
[0095] Example 10
[0096] Raw material preparation: In a glove box under nitrogen protection, weigh 3.0g of FAI and 6.27g of PbI2 according to the stoichiometric ratio of FAPbI3, add 0.371g of oleic acid (4wt% of the total material mass) as an auxiliary agent, and mix evenly to obtain a mixture.
[0097] Grinding jar sealing: Place the mixture into a 100mL zirconia grinding jar, add zirconia grinding balls (70% small balls with a diameter of 1mm and 30% large balls with a diameter of 5mm), and adjust the mass ratio of grinding balls to the mixture to 7:1 (i.e., 65.5g of grinding balls). Purge the jar with nitrogen to replace the air, continue for 6 minutes, then seal the jar, maintaining the inert atmosphere pressure inside the jar at 0.15MPa.
[0098] Ball milling reaction: The grinding jar was fixed on the planetary disk of a planetary ball mill, and the ball mill was started. The total ball milling time was 10 hours. For the first 10 / 3 hours (1 / 3 of the total time), the speed was 600 rpm, and for the next 20 / 3 hours (2 / 3 of the total time), the speed was reduced to 400 rpm. The jar temperature was monitored and controlled in real time through a circulating water cooling system to keep it ≤46℃, and the pressure fluctuation inside the jar was ≤±0.03MPa.
[0099] Post-processing: After ball milling, the product was removed and sieved through a 2000-mesh sieve to separate the grinding balls from the perovskite powder. The sieved powder was placed in a container, and ethanol was added at a solid-liquid ratio of 1g:10mL. The mixture was ultrasonically vibrated for 10 minutes to disperse the agglomerated particles. The washing operation was repeated 3 times, at which point the transmittance of the washing solution reached 96.8%. The washed powder was dried at 40℃ and a vacuum of -0.1MPa for 2 hours to obtain FAPbI3 perovskite powder.
[0100] Product characteristics: The powder particle size is 50nm to 500nm, and X-ray diffraction analysis shows that the crystallinity is 97.8%.
[0101] Comparative Example 1
[0102] Raw material preparation: Same as in Example 1 (FAI 1.58g, PbI2 3.31g, oleic acid 0.049g).
[0103] Grinding jar sealing: Same as in Example 1 (grinding ball mass ratio 10:1, gradation 7:3, argon purging for 5 minutes, pressure 0.2MPa).
[0104] Ball milling reaction: Total time 6 hours, 800 rpm for the first 2 hours and 300 rpm for the last 4 hours, but the temperature was not controlled (the actual tank temperature rose to 65℃), and the pressure fluctuated by ±0.04MPa.
[0105] Post-processing: Same as in Example 1 (500-mesh sieve, 3 washes with ethanol, and drying under the same conditions).
[0106] Product characteristics: Powder particle size 1.5-3μm, crystallinity 88.6% (XRD shows obvious impurity peaks), and the transmittance of the washing solution is 92% (there are many residual additives).
[0107] Comparative Example 2
[0108] Raw material preparation: Same as in Example 2 (FAI 3.16g, PbI2 6.62g, low melting point quaternary ammonium salt 0.293g).
[0109] Grinding jar sealing: The grinding ball gradation was changed to 5:5 (mass ratio) of 1mm diameter small balls and 5mm large balls, and the rest was the same as in Example 2 (mass ratio 15:1, nitrogen purging for 6 minutes, pressure 0.15MPa).
[0110] Ball milling reaction: Same as in Example 2 (12 hours, 600 rpm for the first 4 hours and 200 rpm for the last 8 hours, temperature ≤50℃).
[0111] Post-processing: Same as in Example 2 (800-mesh sieve, ethanol washing twice).
[0112] Product characteristics: The powder has an uneven particle size distribution (200nm~3μm), a crystallinity of 90.3% (irregular grain growth), and obvious agglomeration.
[0113] Comparative Example 3
[0114] Raw material preparation: Same as in Example 3 (FAI 0.79g, PbI2 1.65g, no additives), but operated in air (without inert atmosphere protection).
[0115] Grinding jar sealing: Same as in Example 3 (mass ratio 5:1, argon purging for 3 minutes, pressure 0.3MPa, but in reality, due to residual air, the oxygen content inside the jar is >5%).
[0116] Ball milling reaction: Same as in Example 3 (3 hours, 700 rpm for the first hour and 400 rpm for the last 2 hours, temperature ≤48℃).
[0117] Post-processing: Same as in Example 3 (200-mesh sieve, ethanol washing twice).
[0118] Product characteristics: The powder is yellowish-brown (due to oxidation of the raw material), with a particle size of 800 nm to 2.5 μm and a crystallinity of 89.7% (containing PbO impurity phase).
[0119] Comparative analysis of comparative examples and Examples 1-10
[0120] Comparative Example 1 vs Examples 1-10: Due to the lack of temperature control in Comparative Example 1 (exceeding 50°C), the perovskite grains excessively grew and partially decomposed, resulting in a crystallinity that was 5%-8% lower than that of the Examples (95.5%-98.1%), with larger and wider grain sizes. The Examples, through strict temperature control of ≤50°C using circulating water cooling, ensured stable grain growth.
[0121] Comparative Example 2 vs Examples 1-10: Comparative Example 2 changed the grinding ball gradation (deviating from 7:3). The insufficient proportion of small balls led to incomplete raw material crushing, while the excessive proportion of large balls inhibited uniform grain growth. The product particle size distribution span (2.8 μm) was 1.6 times that of Examples (maximum 1.7 μm), and the crystallinity was 5% to 8% lower. The gradation design of Examples balanced crushing efficiency and grain growth, resulting in more uniform particle size.
[0122] Comparative Example 3 vs Examples 1-10: Due to the lack of an inert atmosphere protection, the raw materials (especially PbI2) in Comparative Example 3 were oxidized to form impurity phases, resulting in a 6%–8% lower crystallinity compared to the Examples, and the powder contained impurities, leading to abnormal color. The Examples, through the control of an inert atmosphere (argon / nitrogen) and sealing pressure, effectively avoided oxidation, resulting in higher product purity.
[0123] Beneficial effects of Examples 1 to 10
[0124] High crystallinity and high purity: The crystallinity of all products in the examples was >95.5% (up to 98.1%), which was much higher than that of the comparative examples (88.6% to 90.3%), and there were no impurity phases (no impurity peaks in XRD). This is due to the strictly controlled ball milling temperature (≤50℃), inert atmosphere protection, and stepwise rotation speed design (high at the beginning and low at the end), which ensured the full reaction of the raw materials and avoided grain decomposition or oxidation.
[0125] Controllable and uniform particle size distribution: The product particle size is precisely controlled within the range of 50 nm to 2 μm, with a span of ≤1.8 μm (e.g., only 450 nm in Example 10), which is far superior to the wide distribution (200 nm to 3 μm) of Comparative Example 2. This is attributed to the 7:3 grinding ball gradation (efficient crushing of small balls and promotion of uniform growth of large balls) and the sieving process (200 to 2000 mesh to suit different particle size requirements).
[0126] Process stability and repeatability: By controlling pressure fluctuations (≤±0.05MPa), wash liquid transmittance (≥95%), and drying conditions (40℃, -0.1MPa), the batch-to-batch product performance deviations were ≤1.2% (crystallinity) and ≤50nm (particle size), thus solving the performance fluctuation problem caused by parameter loss in the comparative example.
[0127] Synergistic optimization effect of additives: Examples (1-2, 4-6, 8, 10) with added oleic acid or low melting point quaternary ammonium salt (0.1% to 5 wt%) showed a 1% to 2% increase in crystallinity and a 10% to 20% reduction in particle size compared to examples (3, 9) without additives. This indicates that the additives can effectively promote grain dispersion and growth, and the dosage is controllable with no residue (removed by washing with ethanol).
[0128] In summary, the perovskite powders prepared in Examples 1-10 by precisely controlling the ball milling parameters, atmosphere, and post-processing techniques are significantly superior to the comparative examples in terms of crystallinity, particle size uniformity, and purity, making them suitable for large-scale production and optoelectronic device applications.
[0129] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing organic or inorganic perovskite by ball milling, characterized in that, The method includes: Step 1: In a glove box protected by an inert atmosphere, weigh the organic and inorganic raw materials according to the stoichiometric ratio of perovskite, and selectively add additives to obtain a mixture; place the mixture in a ball mill equipped with a zirconia grinding jar and zirconia grinding balls and seal it. Step 2: Place the sealed grinding jar from Step 1 into a planetary ball mill and ball mill it at a speed of 200 rpm to 800 rpm for 1 to 12 hours; wherein the mass ratio of grinding balls to material is 5:1 to 20:1, and the grinding balls are composed of small balls with a diameter of 1 mm and large balls with a diameter of 5 mm in a mass ratio of 7:3; the ball milling temperature is controlled at ≤50℃. Step 3: Take out the product after ball milling reaction in step 2, sieve it, wash it with ethanol to remove residual additives, and then vacuum dry the washed product at 40°C for 2 hours to obtain crystalline perovskite powder.
2. The method for preparing organic or inorganic perovskite by ball milling according to claim 1, characterized in that, Step 1: In a glove box under an inert atmosphere, weigh the organic and inorganic raw materials according to the stoichiometric ratio of perovskite, and selectively add additives to obtain a mixture, including: Step 11: In a glove box protected by an inert atmosphere, weigh out the organic component AX and the inorganic component BX2 according to the stoichiometric ratio of the perovskite chemical formula ABX3, where A is formamidinyl, B is lead ion, and X is iodide ion. Step 12: Selectively add 0.1 to 5 wt% of the total mass of the materials as an auxiliary agent; Step 13: Place the mixture and zirconia grinding balls together into a zirconia grinding jar and seal the jar to maintain an inert atmosphere.
3. The method for preparing organic or inorganic perovskite by ball milling according to claim 2, characterized in that, The mixture is placed in a ball mill equipped with a zirconia grinding jar and zirconia grinding balls and sealed, including: The mixture obtained in step 13 is loaded into the zirconia grinding jar, and zirconia grinding balls are added; Control the gradation of the grinding balls, with 1mm diameter small balls accounting for 70% of the total mass of the grinding balls and 5mm diameter large balls accounting for 30%; Adjust the mass ratio of grinding balls to the mixture to 5:1 to 20:1; Inert gas is introduced into the grinding jar to replace the air for more than 3 minutes; The tank is sealed, and the pressure of the inert atmosphere inside the tank is maintained at 0.1 to 0.3 MPa.
4. The method for preparing organic or inorganic perovskite by ball milling according to claim 3, characterized in that, Step 2: Place the sealed grinding jar from Step 1 into a planetary ball mill and ball mill at a speed of 200 rpm to 800 rpm for 1 to 12 hours; wherein the mass ratio of grinding balls to material is 5:1 to 20:1, and the grinding balls consist of small balls with a diameter of 1 mm and large balls with a diameter of 5 mm in a mass ratio of 7:3; the ball milling temperature is controlled at ≤50℃, including: Secure the sealed grinding jar to the planetary disk of the planetary ball mill and start the ball mill; The ball mill is operated at speeds ranging from 200 rpm to 800 rpm, wherein: For the first third of the time: control the rotation speed at 600-800 rpm to promote raw material crushing and initial reaction; In the last two-thirds of the time: reduce the speed to 200-400 rpm to optimize grain growth and crystallinity; The tank temperature is monitored in real time and maintained at ≤50℃ through a circulating water cooling system. The total ball milling time is 1 to 12 hours, during which the pressure fluctuation of the inert atmosphere inside the tank is ≤ ±0.05 MPa.
5. The method for preparing organic or inorganic perovskite by ball milling according to claim 4, characterized in that, Step 3: The product from the ball milling reaction in Step 2 is taken out, sieved, washed with ethanol to remove residual additives, and then vacuum dried at 40°C for 2 hours to obtain crystalline perovskite powder, comprising: The product after ball milling in step 2 is sieved through a 200-2000 mesh sieve to separate the grinding balls from the perovskite powder. Place the sieved powder in a container, add ethanol at a solid-liquid ratio of 1g:10mL, and sonicate for 5-10 minutes to disperse the agglomerated particles. Repeat the washing process 2 to 3 times until the light transmittance of the washing solution is ≥95%; The washed powder was dried at 40℃ and under a vacuum of -0.1MPa for 2 hours to obtain perovskite powder with a particle size of 50nm to 2μm and a crystallinity of >95%.
6. The method for preparing organic or inorganic perovskite by ball milling according to claim 5, characterized in that, The additive is oleic acid or a low-melting-point quaternary ammonium salt.
